ORGANISASI SEKOLAH YANG VISIONER - Hambali, Muh. (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
School organization is an institution that manages aspects of knowledge, attitude, and skills of students. The organization not only has responsible about learning, but also responsible about condition of school that encourage changes in how to manage the headmaster. Headmaster is the main driver of school organization. To be visionary school organization needs the characteristic of organization both of mechanic and organic. Headmaster needs strong capacity to encourage the organization to achieve dynamic tradition and competency at school. That condition has impacts towards structure and culture at school that can respond to the expectation andchallenges in the future. Headmasters who have visionary leadership can manage challenge to be expectation to achieve the goal of school. Besides that, headmaster tries to inspire the stakeholders to be the center of changes every time in order to adapt to technological developments and the needs of industrial society. School organization reflcts the combination between individuals who have the same dream. The duty of headmaster is realizing the expectations ofvision and mission of school. Headmaster showed the visionary characteristic in managing the elementary school organization. Keywords: School Organization, Visionary